Ex aequo et bono as a response to the 'over-judicialisation' of international commercial arbitration - Teramura, Nobumichi (International arbitration law library, 2020)
Ex Aequo et Bono as a Response to the 'Over-Judicialisation' of International Commercial Arbitration' investigates significant divergence in the understanding of ex aequo et bono across state jurisdictions and international arbitration institutions and analyses the core trends in actual legal practice and in thinking about the principle. Despite its many distinguished proponents over time, ex aequo et bono - the idea of deciding disputes on the basis of what an adjudicator regards as fair and equitable - has failed to take hold in international commercial arbitration (ICA). Formalisation and fossilisation of arbitral procedure, as manifested in the increasing use of litigation-style practice, unfortunately reign instead. This bold and challenging book argues that parties to an arbitration should be more willing for their cross-border disputes to be decided (and arbitrators should be more prepared to decide those disputes) in accordance with broad principles of equity and fairness, rather than by strict adherence to technical rules of law.